The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1038/emm.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphic minisatellite region of BORIS regulates gene expression and its rare variants correlate with lung cancer susceptibility

Abstract: Aberrant expression of BORIS/CTCFL (Brother of the Regulator of Imprinted Sites/CTCF-like protein) is reported in different malignancies. In this study, we characterized the entire promoter region of BORIS/CTCFL, including the CpG islands, to assess the relationship between BORIS expression and lung cancer. To simplify the construction of luciferase reporter cassettes with various-sized portions of the upstream region, genomic copies of BORIS were isolated using TAR cloning technology. We analyzed three promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…also observed different behaviors of tumor cells upon aberrant expression of BORIS29. The isoform variants of BORIS may function differently in different cell backgrounds3031. Colorectal cancer is a heterogeneous multi-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…also observed different behaviors of tumor cells upon aberrant expression of BORIS29. The isoform variants of BORIS may function differently in different cell backgrounds3031. Colorectal cancer is a heterogeneous multi-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Since 5-FU or DDP induces DNA damage and apoptosis of carcinoma cells ( 9 11 ), BORIS may induce resistance to DDP therapy. Based on the prevalent expression of BORIS and the high incidence of DDP resistance in NSCLC ( 4 , 12 ), it is worth investigating whether BORIS contributes to DDP resistance in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, it expresses only in testicular tissue participating in spermatogenesis. In multiple tumor tissues and cells, it also could be rehighly expressed, being involved in tumorigenesis, metastasis and invasion 2–4 . BORIS usually binds to the gene promoter region to regulate the expression of tumor related genes.…”
Section: Introductionmentioning
confidence: 99%
“…In multiple tumor tissues and cells, it also could be rehighly expressed, being involved in tumorigenesis, metastasis and invasion. [2][3][4] BORIS usually binds to the gene promoter region to regulate the expression of tumor related genes. Our previous study found that BORIS up-regulated the expression of Oct4 by increasing H3K4me2 and reducing H3K27me3, and promoted the stem cell-like properties in HCC cells.…”
Section: Introductionmentioning
confidence: 99%